On the constrained error bound condition and the projected Levenberg–Marquardt method. (3rd August 2017) - Behling, R.; Fischer, A.; Haeser, G.; Ramos, A.; Schönefeld, K.
Abstract : In this paper, we first derive a characterization of the solution set of a continuously differentiable system of equations subject to a closed feasible set. Assuming that a constrained local error bound condition is satisfied, we prove that the solution set can locally be written as the intersection of a differentiable manifold with the feasible set. Based on the derivation of this result, we then show that the projected Levenberg–Marquardt method converges locally R-linearly to a possibly nonisolated solution under significantly weaker conditions than previously done.